Fair referee assignments for professional football leagues - Yavuz, Mesut; Inan, Umut H.; Figlali, Alpaslan (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Assignment of referees to football games is an important problem faced in professional football leagues. Despite its importance, the problem has received limited academic attention. This paper presents a model and analysis of the problem for fair referee assignments, and develops a constructive heuristic and a local search procedure for its solution. Results from an extensive computational study show that the methods are effective in solving the problem in a second of computation time and yielding an excellent solution quality. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: referee assignment; sports; heuristics; local search; Computer Science; Engineering; Operations Research & Management Science